New Approaches to the Study of Esotericism - Asprem, Egil; Strube, Julian (Supplements to Method & Theory in the Study of Religion, 2020)
This volume offers new approaches to some of the biggest persistent challenges in the study of esotericism and beyond. Commonly understood as a particularly "Western" undertaking consisting of religious, philosophical, and ritual traditions that go back to Mediterranean antiquity, this book argues for a global approach that significantly expands the scope of esotericism and highlights its relevance for broader theoretical and methodological debates in the humanities and social sciences. The contributors offer critical interventions on aspects related to colonialism, race, gender and sexuality, economy, and marginality. Equipped with a substantial introduction and conclusion, the book offers textbook-style discussions of the state of research and makes concrete proposals for how esotericism can be rethought through broader engagement with neighboring fields. Readership: All interested in the study of esotericism, ranging from established experts and teachers looking for textbook introductions to students aiming to familiarize themselves with current discussions within the field.